Quality of Life After Caustic Ingestion. Issue 6 (December 2021) - Faron, Matthieu; Corte, Helene; Poghosyan, Tigran; Bruzzi, Matthieu; Voron, Thibault; Sarfati, Emile; Cattan, Pierre; Chirica, Mircea
Abstract : Objective: The aim of the study was to evaluate long-term QOL after caustic ingestion. Background: Caustic ingestion strongly affects patient's QOL but data on the topic is scarce in the literature. Methods: QOL evaluation was conducted in survivors from a large cohort of patients with caustic injuries. QOL was assessed using the EORTC QLQ-OG25 module, the SF12v2 score, and the hospital anxiety and depression scale questionnaire. One hundred thirty-four patients (59 men, median age 43) completed the survey; 72 (54%) patients underwent emergency digestive resection and in 99 (74%) patients underwent esophageal reconstruction. Results of QOL questionnaires were compared to average values determined in healthy volunteers and in patients with esophageal cancers. Results: The median QLQ-OG25 score was 44 (34, 62) and values were significantly lower when compared to a normal population ( P < 0.0001). SF12v2 scores were significantly inferior to those expected in a normal population on both the physical component summary (PCS) (43.3 ± 10.8; P < 0.0001) and the mental component summary (44 ± 9.7; P < 0.0001) scales. Emergency esophageal resection was significantly associated with higher QLQ-OG25 scores ( P < 0.0001), but not with mental component summary ( P = 0.3), PCS ( P = 0.76), HAD anxiety ( P = 0.95), and HAD depression scores ( P = 0.59); results were similar after extended emergency resection. When compared to esophagocoloplasty alone, pharyngeal reconstruction had a significant negative impact on QLQ-OG25 ( P < 0.0001), PCS ( P = 0.01), and HAD depression ( P = 0.0008) scores. Conclusions: QOL is significantly impaired after caustic ingestion. QOL issues should not influence the emergency surgical strategy but deserve discussion before esophageal reconstruction for caustic injuries. Abstract : Supplemental Digital Content is available in the text